Mechanical and Electrical Properties of Silicone Rubber Based Composite for High Voltage Insulator Application - Kamarudin, Najwa; Abd Razak, Jeefferie; Mohamad, Noraiham; Norddin, Nurbahirah; Aman, Aminuddin; Muzafar Ismail, Mohd; Junid, Ramli; Chew, Tony (International Journal of Engineering and Technology, 2018)
The silicone rubber (SiR) based composites has grown increasing demand in high voltage insulation application due to their exceptional ability in tackling drawbacks of existing ceramic types insulator. This paper showcase the experimental findings to understand the mechanical and electrical behavior of silicone rubber filled with various types of mineral fillers (SiO2, CaCO3, and CaSiO3) specifically for high voltage insulator application. The properties variation for both mechanical and electrical attributes were analysed throughmechanical tensile testing and surface resistivity testing. Addition of mineral fillers into silicone rubber at different weight percentages (5, 10, 20, 30, 40) wt.% had caused that, as filler loading increased, the mechanical tensile performance was significantly decreased. This is due to weak reinforcing action and gap formation which found between fillers and rubber macromolecules that cause weaker cohesion between the rubber-filler components. While the value of surface resistivity is found to increase as the filler loading increased. Integration of silicone rubber with mineral fillers has resulted in no improvement of mechanical properties, but having a good surface resistivity. This interesting phenomenon was further explained by the fracture morphology evaluation via Scanning Electron Microscope (SEM) observation. From these preliminary studies, it can be concluded that, for SiR based composite system, the resulted mechanical properties and electrical properties are not interconnected between each other and both attributes are stand alone with regards to the effect of filler loading for various mineral filler types.Â